Vehicle Testing and Development Involving a Simplified Split Cooling with Integrated Exhaust Heat Recovery and Reuse - Osman, A. (SAE International, 2016)
Additional fuel consumption reduction during the NEDC test cycle and real life driving can be effectively achieved by quickly raising the temperatures of the powertrain's parts, oils and coolant closer to the optimal operating temperatures. In particular, the engine cooling system today must play a bigger role in the overall thermal management of the powertrain's fluids and metals during warm-up, idle and severe operating conditions. In responding to these additional requirements, the previously proposed cost effective split cooling system has been further evolved to expedite the powertrain's warming up process without compromising the overall heat rejection performance during severe operating conditions. In achieving these warming and cooling functions, the coolant flow rate in the cylinder head is almost stagnant when the single thermostat is closed and at its maximum when the thermostat is fully opened. In this context, the constantly flowing engine oil above the cylinder head's water jacket can be warmed up and cooled by these differing coolant flow rates and temperatures. Unlike other conventional split cooling circuits, the coolant flow rate in the cylinder block is constantly flowing thus allowing heat transfers to take place between the recirculated coolant to the cabin heater and CVT oil heat exchanger. In speeding up the warming up process involving the CVT oil, additional heat is obtained from the exhaust gas via the turbocharger housing with reversible coolant flow. During the vehicle testing and development, the test vehicles were subjected to various tests and the temperatures of various powertrain fluids and metals were measured at various locations and compared with the baseline. From the tests conducted, the proposed cooling system significantly enhanced the thermal management efficiency and effectiveness of the vehicles while reducing the cost and complexity of the overall cooling system. Copyright Â© 2016 SAE International.